1983
DOI: 10.1126/science.6356363
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein-Human GH Fusion Genes Stimulate Growth of Mice

Abstract: The promoter or regulatory region of the mouse gene for metallothionein-I was fused to the structural gene coding for human growth hormone. These fusion genes were introduced into mice by microinjection of fertilized eggs. Twenty-three (70 percent) of the mice that stably incorporated the fusion genes showed high concentrations of human growth hormone in their serum and grew significantly larger than control mice. Synthesis of human growth hormone was induced further by cadmium or zinc, which normally induce m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(168 citation statements)
references
References 30 publications
13
154
1
Order By: Relevance
“…In contrast, the day of vaginal opening advanced by 7-8 days hGH, and Line 2 had relatively low levels. Most mice expressing a transgene of GH from various species show an increase in growth rate [20]. In this study, transgenic rats secreting hGH at higher levels (Lane 1) had body weight increases that indicate a growth promoting effect of hGH on the rat.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…In contrast, the day of vaginal opening advanced by 7-8 days hGH, and Line 2 had relatively low levels. Most mice expressing a transgene of GH from various species show an increase in growth rate [20]. In this study, transgenic rats secreting hGH at higher levels (Lane 1) had body weight increases that indicate a growth promoting effect of hGH on the rat.…”
Section: Resultsmentioning
confidence: 66%
“…GH producing cells (somatotorophs) in the pituitary disappear in transgenic mice secreting hGH [20]. It is also possible that low rGH levels in our transgenic rats were due to inhibition of somatotoroph proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We report here inducible liver pathologies in transgenic mice expressing the PMLRARa protein driven by the mouse MT promoter. This promoter had been previously shown to e ciently direct transgene expression in a wide variety of murine tissues as well as to be inducible by heavy metals (Heisterkamp et al, 1990;Palmiter et al, 1983Palmiter et al, , 1985Crenshaw et al, 1987;Jhappan et al, 1990;Sandgren et al, 1990). Nine of the 10 founder mice lines resulting from MT-PMLRARa transgene injection were considered as nonexpressors.…”
Section: Discussionmentioning
confidence: 99%
“…Lanes 5 and 9 ± normal medium +2% FCS + 100 mg Zn 2+ (Figure 7, lanes 6 and 7). It was shown that 25 mM of ZnSO 4 in the drinking water can activate the metallothionein promoter in transgenic mice (Palmiter et al, 1983). However, Zn 2+ did not seem either to in¯uence the growth or the H19 expression level in the tumors that arose from original and transfected cells (Figure 6, lanes 2 and 3; Figure 7, lanes 2 and 3).…”
Section: Transfection Of a Non-h19 Expressing Clone With An H19 Exprementioning
confidence: 95%